2021
DOI: 10.1371/journal.pone.0257882
|View full text |Cite
|
Sign up to set email alerts
|

Angler and environmental influences on walleye Sander vitreus and muskellunge Esox masquinongy angler catch in Escanaba Lake, Wisconsin 2003–2015

Abstract: Angler trip success and catch rates are dependent upon a fishes’ vulnerability to angling. Angling vulnerability can be influenced by angler-specific attributes (i.e., bait choice, lure size, use of a guide), and individual fish traits (i.e., boldness, aggression, stress responsiveness, and memory retention). The mechanisms that function in a fishes’ angling vulnerability, and contribute to catch rate, are likely correlated with environmental factors however, the influence of environmental factors on angling v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
(127 reference statements)
0
4
1
Order By: Relevance
“…The CPUE in the current study was higher than those in comparable studies with wild populations (see the Supplement available in the online version of this article), although the density of fish in the present study was likely higher than that of wild populations (Shaw et al. 2021). Reasons for the trends in capture during the current study are not known, but we propose three possible explanations.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The CPUE in the current study was higher than those in comparable studies with wild populations (see the Supplement available in the online version of this article), although the density of fish in the present study was likely higher than that of wild populations (Shaw et al. 2021). Reasons for the trends in capture during the current study are not known, but we propose three possible explanations.…”
Section: Discussioncontrasting
confidence: 70%
“…Finally, among the appealing factors that make Muskellunge a popular target for anglers are their wariness and difficulty to catch, and there may be other factors not assessed here that may drive capture. For example, Shaw et al (2021) analyzed a 12-year data set of Muskellunge capture on Escanaba Lake, Wisconsin, and found that factors such as the use of live bait, lunar phase, and barometric pressure all influenced the capture of Muskellunge, but these factors were not accounted for in the current study design. Although the exact mechanism for low overall capture is not clear, the present study was successful in capturing fish relative to other work conducted with wild Muskellunge.…”
Section: Metricmentioning
confidence: 98%
“…This increased capture may be a result of several factors, such as the internal state of the fish, overlap of the fish with fishing gear, and gear selectivity (Lennox et al, 2017). For example, the capture of muskellunge in a Wisconsin lake increased when populations were fished in specific lunar positions (overhead or underfoot), at dusk, and at lower wind speeds, perhaps because these environmental conditions influenced prey‐fish activity that caused muskellunge to be vulnerable to angling (Shaw et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Besides walleye, the fish assemblage includes naturally reproducing populations of muskellunge Esox masquinongy , northern pike Esox lucius , smallmouth bass Micropterus dolomieu , yellow perch, bluegill Lepomis macrochirus , pumpkinseed Lepomis gibbosus , rock bass Ambloplites rupestris , white sucker Catostomus commersonii , bluntnose minnow Pimephales notatus , and common shiner Luxilus cornutus . Since 1946, Escanaba Lake has been used as an experimental lake to test for species‐specific harvest regulations (Patterson, 1953 ) and has maintained a compulsory creel census of all anglers fishing the lake (Shaw et al., 2021 ). Experimental regulations for walleye on Escanaba Lake originated with no regulation on length and harvest (1946–2003) and were changed to a 71‐cm minimum length limit with a daily bag limit of one fish in 2003 (Hansen et al., 2011 ), which was maintained through the 2021 fishing season.…”
Section: Methodsmentioning
confidence: 99%